The Development Studies on Islamic Economic Education Based on Local Wisdom in Indonesia: A Multicultural Approach - Ayif Fathurrahman (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2023)
This article focused on the development of islamic economic education in Indonesia with a multicultural approach. It tries to reaffirm Islam's universal values and adjust them to local values that have long been entrenched in the midst of Indonesian multicultural society. This descriptive qualitative research used data sources from literature or library research. The normative approach was applied to examine the ideals of the Islamic Economic conception and then analyzed how it is applied. The result of this research regarding the urge to develop islamic economics based on a multicultural perspective: firstly, it is because of the emergence of the globalization era and postmodern culture. Secondly, the reality of Indonesian plurality, apart from syiar, is used to explore the local genius in socio-economic in Indonesia. Islamic economic education with a multicultural approach is a progressive approach to transform education that holistically provides criticism and shows the weaknesses of Islamic economic education. Islamic economic education based on local values as an instrument of social adjustment encourages the administrators of Islamic economics to play a role in instilling the awareness of the multicultural community to realize a level of comprehension of inclusive Islamic economics.